Two different sources of inequalities: Profits and rents in advanced market economies - Péter Mihályi; Iván Szelényi (Hungarian Academy of Sciences, Institute of Economics, 2016)
The starting point of our research is Piketty (2014) who follows Marx by asserting that rents are merely one of the forms of profits, therefore they do not require separate conceptual analysis and statistical separation. Speaking of the generation of rents (as a distinctly different mechanism from profit maximising business activity), we use a broader notion of rent than it was customary in the past 50 years. We return to the Ricardian tradition and define the institution of rent as payments for goods, services or for work in employment that exceed the competitive price. Our rent concept includes - inter alia - the income of those whose jobs are protected by unions or professional associations, with the same holding for top-managers or celebrities of the entertainment industry. We also show that state-generated oligopolies are not necessarily evil, as they are often justified by other social objectives than equity. To conclude, three main propositions are presented: (i) rents are not anomalies of the advanced market economies, they are indispensable building blocks of it; (ii) rents are not the privilege of large companies and their owners; (iii) rents, rather than profits are the main driving force of the increase of wealth inequalities since the 1970s
Keywords: B12; D63; E01; 330; inequality; capital; capitalism; profits; rents